Depression moderates the associations between beliefs about medicines and medication adherence in patients with rheumatoid arthritis: Cross-sectional study. (August 2018) - Brandstetter, Susanne; Riedelbeck, Gertraud; Steinmann, Mark; Loss, Julika; Ehrenstein, Boris; Apfelbacher, Christian
The 'necessity–concerns framework' postulates that patients' adherence behaviour is influenced by beliefs about the necessity and the concerns patients have regarding their prescribed medicines. We hypothesized that depression moderates the associations between beliefs about medicines and medication adherence among people with rheumatoid arthritis. Using multivariate logistic regression, we observed that people experiencing more depressive symptoms showed stronger associations between necessity beliefs and adherence as well as attenuated associations between concerns and adherence, respectively, in a cross-sectional sample ( N  = 361). Thus, depression moderates the associations postulated in the 'necessity–concerns framework' in a differential way in people with rheumatoid arthritis.